An Optimal Method of Iron Starvation of the Obligate Intracellular Pathogen, Chlamydia Trachomatis - Thompson, Christopher C.; Carabeo, Rey (Frontiers in Microbiology, 2011)
Iron is an essential cofactor in a number of critical biochemical reactions, and as such, its acquisition, storage, and metabolism is highly regulated in most organisms. The obligate intracellular bacterium, Chlamydia trachomatis experiences a developmental arrest when iron within the host is depleted. The nature of the iron starvation response in Chlamydia is relatively uncharacterized because of the likely inefficient method of iron depletion, which currently relies on the compound deferoxamine mesylate (DFO). Inefficient induction of the iron starvation response precludes the identification of iron-regulated genes. This report evaluated DFO with another iron chelator, 2,2’-bipyridyl (Bpdl) and presented a systematic comparison of the two across a range of criteria in a single-treatment time-of-infection regimen. We demonstrate that the membrane permeable Bpdl was superior to DFO in the inhibition of chlamydia development, the induction of aberrant morphology, and the induction of an iron starvation transcriptional response in both host and bacteria. Furthermore, iron starvation using Bpdl identified the periplasmic iron binding protein-encoding ytgA gene as iron- responsive. Overall, the data present a compelling argument for the use of Bpdl, rather than DFO, in future iron starvation studies of chlamydia and other intracellular bacteria.